Ischemic and bleeding risk stratification in diabetic patients after acute coronary syndrome based on insulin requirement. (25th November 2020) - Cavallari, I; Sagazio, E; Antonucci, E; Calabro', P; Gragnano, F; Cirillo, P; Gresele, P; Palareti, G; Pengo, V; Pignatelli, P; Marcucci, R; Patti, G
Abstract: Background: Diabetes is a known risk factor for a first or recurrent cardiovascular event, however, its association with an increased risk of bleeding is controversial. To date, no study has explored the prognostic weight of insulin therapy in the setting of ACS. Purpose: To investigate the differential role of insulin versus no insulin therapy on ischemic and bleeding risks in patients with diabetes and ACS. Methods: START-ANTIPLATELET is a prospective, real-world multicenter registry including consecutive patients admitted for ACS. For the purpose of this analysis, patients were stratified according to diabetes status and insulin therapy. We compared 1-year rates of major adverse cardiovascular events, a composite of cardiovascular death, myocardial infarction and stroke, and of any bleeding, according to diabetes status (no diabetes, diabetes not on insulin therapy, diabetes on insulin therapy). In addition, we evaluated the net clinical benefit of dual antiplatelet therapy with the newer P2Y12 inhibitors (ticagrelor or prasugrel) vs dual antiplatelet therapy with clopidogrel according to diabetes status. Results: In an overall population of 907 patients, 198 had diabetes, 10.6% of whom were on insulin. From non-diabetic patients to diabetic patients not on insulin and diabetic patients on insulin there was a stepwise decrease of MACE-free survival (log-rank p 0.039) with incidence of events at 1 year being 3.8%, 6.8% (adjusted p vs no diabetes 0.49) and 12.5% (adjusted p vs no diabetes 0.047), respectively (Figure, panel A). The rates of any bleeding were higher in patients on insulin (20.8% vs 8.8% in those without diabetes and 5.8% in diabetic patients not receiving insulin; log-rank p 0.028; Figure, panel B). Multivariable analysis demonstrated an almost 5-fold increase of any bleeding in diabetic patients with vs without insulin (OR 4.98, 95% CI 1.46–16.92; p=0.010). In the overall population, the incidence of the net composite endpoint including MACE or major bleeding with the use of ticagrelor/prasugrel on top of aspirin was significantly lower compared to use of clopidogrel (4.7% vs 8.4%; OR 0.54, 95% CI 0.30–0.94, p=0.031). This net clinical benefit in patients receiving a newer P2Y12 inhibitor was regardless of the diabetes status (p for interaction 0.48). Conclusions: In this cohort of ACS patients, the presence of diabetes stratified by insulin therapy was associated with a graded increase in the 1-year rates of MACE. Conversely, insulin therapy significantly contributed to the overall increase of bleeding risk in diabetes. Funding Acknowledgement: Type of funding source: None